Três ensaios em economia da saúde - Santos, Anderson Moreira Aristides dos (2016)
This doctoral dissertation presents three independent essays. At first, this paper analyzes the income-related inequalities and inequities in children’s health care, in the city of Pelotas, using longitudinal data from follows-up of 12 to 72 months. The methodology was based on concentration indexes (CI) and their decompositions. The main results showed that there are pro-rich inequalities and inequalities for all analyzed cases. The variables, which mostly contributed to the pro-rich inequity of health insurance and health insurance expenses, are income, asset index and mother’s education. In addition to these three variables, private health insurance (pro-rich) and child’s health variables (pro-poor) have a strong contribution in the CI of medicine use and expenses on medicines. There were reductions in inequality and inequity in the follow-up of 72 months. This reduction occurred with a higher gain or smaller decrease for the poor in health care variable. The second study analyzes the impact of Family Health Program (PSF) on the children’s health (under 12 years old) in Brazil’s rural area, using data from the PNAD (2008) and the PSM and OLS methods, applying sensitivity analysis proposed by Ichino et al. (2008) and Oster (2015). The results indicate that the PSF has statistically significant and high magnitude impact on the children’s health in Brazil’s rural area. However, it is concentrated in the North and Northeast regions, and, it is not significant in the Mid-South region. For the North region, this impact is independent of age, while in the Northeast is significant for younger age groups. The sensitivity analysis proposed by Ichino et al. (2008) reported robust results for the North region in all age groups, while in the Northeast region the robustness only occurred for children between 0 and 3 years old. Based on Oster’s (2015) approach, only the results of the North region in the smaller age groups were robust. Thus, there is confirmation of the hypothesis that this type of health care policy benefits the individuals of the poorest regions in the rural area. The aim of the third essay was to analyze the relationship between demand for imports of pharmaceutical chemicals and pharmaceutical and economic variables (exchange rate, import prices and aggregate income), using elasticities of the demand for imports, considering monthly data for the period 1997-2014 in Brazil. The regressions are estimated by Vector Error Correction model. The main results showed that increases in aggregate income and reductions in import prices have a positive and significant impact, respectively elastic and inelastic way, on imports. The exchange rate was significant only in the aggregate model. Thus, the aggregate income showed a very robust variable and with a strong impact on imports of pharmaceutical chemicals and pharmaceuticals. Considering the argumentation explained in the literature that the deficit in international trade of this industry has relationship with deficits in knowledge and technology, adding to the results found in this dissertation, there is evidence that, when the level of economic activity grows, a greater demand takes place for that type of product and there is no enough domestic production, there is the need for importations, which can generate pressures on the trade deficit in this segment.